AUTOBIOGRAPHICAL ELEMENTS IN AUTOBIOGRAPHICAL NOVELS BY CONTEMPORARY SLOVENIAN FEMALE AUTHORS - Liberšar, Polona (Slavia Centralis, 2026)
The article aims to contribute to a better understanding of contemporary Slovenian women authors, especially those who have published autobiographical works in recent years. Autobiographical elements in these works will be presented as the dominant genre line. The discussion begins with the justification of the term autobiographical novel to render the analysis more in-depth.,. A brief history of the theory of autobiography and similar concepts will also be presented. This is followed by the overview being used as a basis for an analytical-interpretive approach to a few selected works. The results obtained are ultimately used to assess the literary value or triviality of the works.